Reframing Digital Business Training as a Capability-Building Mechanism for SMEs: A Case-Based Analytical Study - Ahmad Abdusalam; Keni Kaniawati (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
Digital transformation has become a strategic imperative for small and medium-sized enterprises (SMEs), yet many digital training initiatives fail to produce sustained business impact. Existing studies often conceptualize training as a mechanism for skill acquisition or technology adoption, offering limited insight into how learning processes translate into strategic capability development. Addressing this gap, this study examines how result-oriented digital business training functions as a capability-building mechanism for SMEs. Using a qualitative case-based analytical approach, the study investigates a structured digital business training program that integrates milestone-based learning design, intensive mentoring, business model experimentation, and financial feasibility analysis. Data were drawn from training modules, mentoring records, iterative business model artifacts, and financial feasibility worksheets. The analysis focuses on identifying learning mechanisms and processual dynamics rather than measuring performance outcomes. The findings reveal that SME capability development emerges through the interaction of multiple learning mechanisms. Result-oriented training design aligns learning activities with real business constraints; mentoring intensity facilitates experiential and adaptive learning; business model experimentation functions as a structured learning process; and financial feasibility analysis serves as a learning artifact that disciplines strategic decision-making. Rather than producing linear outcomes, capabilities develop cumulatively through iterative learning cycles. This study contributes to entrepreneurship and SME literature by reframing digital business training as a strategic learning architecture rather than a skill-transfer intervention. In practice, it offers policymakers and training providers insights into designing digital training programs that foster sustainable capability development. By grounding digital transformation in observable learning processes, the study bridges theory and practice in SME development.